Academic Support at the University of KwaZulu-Natal: A Systematic Review of Peer-Reviewed Journal Articles, 2010–2015 (Journal of Student Affairs in Africa, 2021)
The aim of this systematic review was to examine research studies which focus on effective student support practices and show evidence of credible assessment. To identify effective student support practices, and also to provide a contemporary picture of effective support practices at the University of KwaZuluNatal, 24 studies which met the inclusion criteria were reviewed and analysed in terms of: (i) aims,(ii) main participants, (iii) methodology used and (iv) the main outcomes emerging. The findings from the review indicate that there is a diversity of available evidence, ranging from assessment of peersupport programmes, alternative access programmes to curriculum-based interventions. However, most of these studies are cross-sectional qualitative studies, which also draw from relatively small samples. This suggests that more large-scale studies are needed in the field in order to provide greater insight into effective student support practices. In addition, research which examines academic support programmes over long periods of time while also controlling for programme effects is recommended.
Keywords: student support; academic monitoring and support; systematic review